Dampak Radikalisme terhadap Perempuan Masa Kini - Fajriatun Nisa Islami (FOCUS, 2021)
Radicalism is a deviant thing and has an impact on women. Women are considered to be the perpetrators in an act of violence such as terrorism. In his understanding, radicalism does not only have its own interests, but is very subject to the perspective of the majority. The notion of radicalism can be seen in terms of religion, social, or violent-conflict. Even women have always been the most affected by the existence of radicalism. Therefore, this study aims to discuss Johan Galtung's conflict transformation theory and Peter Neumann's religious violence. This study uses qualitative methods through literature study and descriptive analysis of current radicalism. The results of this study indicate that what Johan Galtung said is related to conflict theory and Peter Neumann, so there must be a basic reference regarding the impact of radicalism on women in every authoritarian government policy in the name of religion and gender.